EXPRESSIVE WRITING IN INDONESIAN CONTEXT - Dinastuti Dinastuti (MANASA, 2018)
As a developing country, Indonesia still struggles to manage its mental health issues. In 2014 the Indonesian government passed the Mental Health Law after five years of delaying, and its goal is to make sure people with mental health issues will be treated better, but there are some unresolved issues such as the economic barriers to gain better mental health care, the social and political unrest, unique but challenging geographic location, the stigma and improper treatments for the mental health patients/clients, and mental health is not a priority yet in many Indonesians. There is also an issue of the failure of reporting mental health related problems, especially in the early stages when minimum intervention would alleviate the symptoms. Expressive writing (EW) as a new intervention could answer some of these circumstances in Indonesian context. This research will use controlled field experiment (pre-test post-test design) with psychodynamic interviewing to see the effectiveness of the expressive writing intervention. To answer experimental hypothesis, t-test will be conducted to evaluate differences between the expressive writing intervention and control writing groups. In analyzing the psychodynamic interview results, the focus will be on moderators of the working mechanism of expressive writing intervention. In conclusion, expressive writing can be a valuable addition to the conventional psychotherapy because it is cost effective, and places minimal burden to the clients.